Study of Extraction Kinetics of Total Polyphenols from Curry Leaves - Patil, S.S. (Hindawi Limited, 2021)
Solid-liquid batch extraction of total polyphenol content from curry leaves (Murraya koenigii L.) was studied in this paper. The effect of different solvent concentrations and temperatures on total polyphenol content was investigated by performing batch experiments. The experimental studies showed that the kinetics of solid-liquid batch extraction was influenced by different solvent concentrations and temperatures. In solid-liquid batch extraction, more recovery of total polyphenols was obtained for 50 (v/v) aqueous methanol and at 333 K temperature. The total polyphenol obtained at optimum conditions was 79.34 mgGAE/L. Mathematical modelling is an important engineering tool used to study the kinetics of extraction as well as in the design of the extraction process to reduce time, energy, and chemical reagents. Peleg and Power law, the two mathematical models, were used to study the kinetics of the batch extraction process. The Peleg model showed the best fit to explain the kinetics of process with R2 > 0.99. Further conventional extraction methods are compared with the novel extraction method. Â© 2021 Sunita S. Patil et al.